INNOVATIONS IN FUNDAMENTAL STUDIES FOR EDUCATION - Kenzhaliev, Bagdaulet; Utelbayev, Bolysbek; Suleimenov, Essen (European Scientific Journal, ESJ, 2015)
This article reviews the influence of new knowledge in natural sciences as it relates to development of innovative technical solutions. It explains the necessity of applying new scientifical concepts to the structure of liquid systems in educating versatile specialists in order to overcome difficulties in creation of effective technical solutions.